Study of Different Polynomial and Matrix Fractions: Exploring the Properties of Polynomial and Matrix Fractions in Linear Systems (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This article illustrates howpolynomials and polynomial matrices can be used to describe linear systems.The focus is put on the transformation to and from the state-space equations,because it is a convenient way to introduce gradually the most importantproperties of polynomials and polynomial matrices, such as: coprimeness,greatest common divisors, unimodularity, column- and row- reducedness,canonical Hermite or Popov forms.